PENGARUH PENDIDIKAN KESEHATAN SECARA INDIVIDUAL TENTANG DIIT TERHADAP PENGETAHUAN DAN KEPATUHAN PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Sri " Rahayu; Sofiana " Nurchayati; Arneliwati " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Patients undergoing hemodialysis should be given health education on diet to create a stable renal function so that no complications. This study aimed to determine the effect of health education on an individually about diet againts knowledge and compliance of patients with chronic renal failure undergoing hemodialysis. This study was use “quasy experimental” research design. The total sample were 30 respondents who taken by using purposive sampling technique. The measuring instrument was use questionnaire about knowledge and compliance about diet which has been tested for validity and reliability. The analysis wereunivariate and bivariate analysis by using dependent, independent t test, mann whitney and wilcoxon. Most characteristics of respondents aged 45-60 years old (70,0%), with the highest gender male (60,0%), last education was senior high school (50,0%), majority of respondent’s job was housewife (36,7 %), most longhemodialysis was 12-60 months (66,7 %).The research result showed knowledge about diet on patients with hemodialysis with p value (0,026) < α (0,05), and compliance about diet with p value (0,000) < α (0,05). The conclusions of this study there was an effect of health education on an individually about diet againts knowledge and compliance of patient with chronic renal failure undergoing hemodialysis. The hemodialysis nurses suggested to provide health education on an individuallybecause each individual has different health problems so that individual health education more effectively and efficiently to improve the knowledge and compliance in hemodialysis patients about his diet.   Keywords  : compliance, diet, health education, hemodialysis, individual method knowledge